2012
DOI: 10.1159/000337210
|View full text |Cite
|
Sign up to set email alerts
|

From Furuncle to Axillary Web Syndrome: Shedding Light on Histopathology and Pathogenesis

Abstract: Axillary web syndrome (AWS) is defined as a cord-like structure extending from the axilla to the medial arm following axillary surgery in women with breast cancer. There is only limited literature on the pathogenesis of this syndrome and the etiology of the cord. A 57-year-old man presented with a band-like skin depression and tightness over the medial aspect of his arm extending from the axilla to the antecubital fossa following development of a furuncle in the ipsilateral axilla. Histopathologic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
1
23
1
1
Order By: Relevance
“…The hypothesis is consistent with the B-type ultrasonography findings, but was not definitive due to the lack of a histopathology report. Most of the investigators were inclined to define the cord-like structure as a lymph vessel [7,8,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis is consistent with the B-type ultrasonography findings, but was not definitive due to the lack of a histopathology report. Most of the investigators were inclined to define the cord-like structure as a lymph vessel [7,8,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…The condition may be related to abnormalities in either the axillary vasculature or the lymphatics[2,3,9]. Anatomic studies of resected cords reveal that these structures may represent dilated and thrombosed lymphatics and/or thrombosed superficial veins[3,9]. The condition is considered to be a variation of Mondor’s disease, a rare thrombophlebitis of the subcutaneous veins caused by trauma such as surgery[10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of dissected cords have shown thrombosed and dilated lymphatics and superficial veins. For this reason AWS may be considered a variant of Mondor's disease, which is a superficial thrombophlebitis presenting with a palpable cord on the breast [2,11,12].…”
Section: Discussionmentioning
confidence: 99%